Low-Frequency Sonophoresis: A Promising Strategy for Enhanced Transdermal Delivery - Divya Marathe; Vasudeva Sampriya Bhuvanashree; Chetan Hasmukh Mehta; Ashwini T.; Usha Yogendra Nayak (Advances in Pharmacological and Pharmaceutical Sciences)
Sonophoresis is the most approachable mode of transdermal drug delivery system, wherein low-frequency sonophoresis penetrates the drug molecules into the skin. It is an alternative method for an oral system of drug delivery and hypodermal injections. The cavitation effect is thought to be the main mechanism used in sonophoresis. The cavitation process involves forming a gaseous bubble and its rupture, induced in the coupled medium. Other mechanisms used are thermal effects, convectional effects, and mechanical effects. It mainly applies to transporting hydrophilic drugs, macromolecules, gene delivery, and vaccine delivery. It is also used in carrier-mediated delivery in the form of micelles, liposomes, and dendrimers. Some synergistic effects of sonophoresis, along with some permeation enhancers, such as chemical enhancers, iontophoresis, electroporation, and microneedles, increased the effectiveness of drug penetration. Sonophoresis-mediated ocular drug delivery, nail drug delivery, gene delivery to the brain, sports medicine, and sonothrombolysis are also widely used. In conclusion, while sonophoresis offers promising applications in diverse fields, further research is essential to comprehensively elucidate the biophysical mechanisms governing ultrasound-tissue interactions. Addressing these gaps in understanding will enable the refinement and optimization of sonophoresis-based therapeutic strategies for enhanced clinical efficacy.